2022
DOI: 10.1002/adfm.202200201
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Framework to Accelerate the Discovery of Perovskites for Solar Thermochemical Hydrogen Production: Identification of Gd Perovskite Oxide Redox Mediators

Abstract: A high‐throughput computational framework to identify novel multinary perovskite redox mediators is presented, and this framework is applied to discover the Gd‐containing perovskite oxide compositions Gd2BB′O6, GdA′B2O6, and GdA′BB′O6 that split water. The computational scheme uses a sequence of empirical approaches to evaluate the stabilities, electronic properties, and oxygen vacancy thermodynamics of these materials, including contributions to the enthalpies and entropies of reduction, ΔHTR and ΔSTR. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…A ferroelectric behavior can thus be induced in superlattices composed of non‐ferroelectric materials. Bare et al [ 12 ] have applied DFT in combination with machine‐learning models to automate the discovery of new candidate materials for thermochemical hydrogen production. Here, a Monte Carlo “rattling” step is introduced in the calculations to correctly model symmetry‐breaking effects due to the oxygen vacancies in perovskite geometries.…”
Section: Electromechanics and Symmetry Breaking In Oxidesmentioning
confidence: 99%
“…A ferroelectric behavior can thus be induced in superlattices composed of non‐ferroelectric materials. Bare et al [ 12 ] have applied DFT in combination with machine‐learning models to automate the discovery of new candidate materials for thermochemical hydrogen production. Here, a Monte Carlo “rattling” step is introduced in the calculations to correctly model symmetry‐breaking effects due to the oxygen vacancies in perovskite geometries.…”
Section: Electromechanics and Symmetry Breaking In Oxidesmentioning
confidence: 99%
“…Bare, Morelock, and Musgrave identified L2MN, GLMN, and G2MN for STCH following a high-throughput compositional screening investigation of Gd-containing and Mn-containing multinary perovskite compositions (GdA′B-B′O 6 , GdA′B 2 O 6 , and Gd 2 BB′O 6 , and AA′MnB′O 6 , AA′Mn 2 O6, and A 2 MnB′O 6 ). 25 The results of that screening are summarized in Section I of the SI, and the investigation's computational framework is briefly described here. We found that the machine-learned tolerance factor τ derived by Bartel et al 32 predicts that L2MN, GLMN, and G2MN are synthesizable as perovskites.…”
Section: Identification Of Mixedmentioning
confidence: 99%
“…However, this technology is currently still held back by the lack of oxide working materials with optimal thermodynamic properties for the two-step reduction–oxidation cycle . While ceria (CeO 2 ) is recognized as the current benchmark system, , it requires undesirably high temperatures to achieve sufficient O deficiency in the reduction step, which has motivated both experimental and computational material design and discovery efforts aimed at either modifying CeO 2 , or identifying suitable new oxides. , However, any gains in improved reduction behavior are offset by deterioration of the oxidation behavior, often dramatically limiting the H 2 generation during the water splitting step to very dilute H 2 /H 2 O ratios well below 1:100, ,, whereas CeO 2 continues to split water even above 1:10. Materials design is often guided by a theoretical performance limit described as a function of specific material properties, such as, in photovoltaics, the Shockley–Queisser limit and extensions thereof. For a defect-mediated solar thermochemical hydrogen (STCH) cycle, for example, current design principles provide little more than the expectation that suitable values of O vacancy formation energies lie in the fairly wide range between 2 and 5 eV. ,, …”
Section: Introductionmentioning
confidence: 99%